Pengaruh Kepemimpinan Transformasional Kepala Sekolah, Disiplin Kerja, Dan Motivasi Kerja Guru Terhadap Kepuasan Kerja Guru (Studi Kasus di Sekolah Dasar Islam Terpadu Insan Permata Lowokwaru) - Muhammad Syaeful Muhaimin; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The study aims to find out and analyze the effects of the influence of the headmaster's transformational leadership, the discipline of work, and the teacher's work motivation on teacher satisfaction (case studies at the Insan Permata Lowokwaru Integrated Islamic Elementary School). The population in this study is all teachers at the Insan Permata Lowokwaru Integrated Islamic Elementary School. The method of collecting data in this study uses a questionnaire with a total of 58 sample respondents. The independent variable in this study is the the effects of transformational leadership, job discipline, and work motivation and contained variables of job satisfaction. The analytical method used in this study is linear regression analysis used by SPSS 22. The results of this study simultaneously indicate that the influence of the headmaster's transformational leadership, job discipline, and teacher's work motivation have both a positive and significant impact on the teacher's job satisfaction. Partially, too, the headmaster's transformational leadership, the teacher's discipline, and work motivation make a significant difference to the teacher's job satisfaction. Keywords: Transformational Leadership, Work Discipline, Work Motivation, And Work Satisfaction